Kualitas Audit dan Auditor Tenure dalam Mendeteksi Manajemen Laba Riil di Bursa Efek Indonesia - Leonardo Davidsi Sipayung (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to determine whether there is an influence between audit quality (measured by the firm size), audit quality (measured by auditor industry specialization), and auditor tenure on real earnings management both partially and simultaneously on the manufacture companies listed on Indonesia Stock Exchange during period 2022 to 2025. Variables used in this study audit quality (measured by the firm size), audit quality (measured by auditor industry specialization) and auditor tenure as independent variable, whereas real earnings management as dependent variable. The population used in this study is the manufacture companies listed om Indonesia Stock Exchange (BEI) during the period 2022 to 2025 as many as 140 manufacture companies. Sampling method used is purposive sampling and 36 sample companies will be the research objects with 144 unit analysis. An analytical technique used in this research is multiple regression analysis. The result of this study indicate that simultaneously audit quality (measured by the firm size), audit quality (measured by auditor industry specialization) and auditor tenure have a positive and significant influences on real earnings management. In partially, audit quality (measured by the firm size) has a positive and significant influence on real earnings management, audit quality (measured auditor industry specialization) has a negative and significant influence on real earnings management and auditor tenure has no significant influence on real earnings management.